Tactical Exercises of The Player in Basketball - qizi, Turg‘unova Dilnura Mamanazar (European Journal of Life Safety and Stability (2660-9630), 2021)
the article provides information about the tactical exercises of a player in baskeltball sports. Also mentioned are the tasks that the player will need during the game.